Optimalisasi Sosialisasi Penggunaan Aplikasi Bogor Traffic Info Dalam Pelaporan Kemacetan Di Wilayah Hukum Polresta Bogor Kota - Panji Wisnu Pamungkas (Police Studies Review, 2020)
Satlantas Polresta Bogor Kota created an innovation for traffic management system, called Bogor Traffic Info which is an application to give service to the people of Bogor City that consists extension of driver license type A and C, traffic accident report, and traffic jam report. The user can download the application on android based cellphone in google playstore. Bogor city is well known for its traffic jam and one of the cause is because it’s the buffer of the capital city of Jakarta. Furthermore, there’s also Kebun Raya Bogor as a world heritage and the President of Indonesia’s palace. There has been 27 traffic jam reports in Bogor City since the launch of the application until February 2020, hence the it’s indicated haven’t been corresponding with the purpose of the innovation. This research is done with the purpose of knowing the use of Bogor Traffic Info application, factors that effect it, and optimization from the use of application’s socialization. This research is done with qualitative approach and the type of research is field research and uses a few theory and concept in resolving problems. The result discovers that the use of Bogor Traffic Info application until now have seven service standard that’s still hasn’t fulfilled the requirements. Factors that affect the innovation, communication channel and social system are inhibit factors on the enhancement of this application. Socialization optimization for the use of Bogor Traffic Info application is done by Satlantas Polresta Bogor Kota with growth strategy, improvement of efficiency strategy, stability strategy and collaboration strategy. Based on the result of research, author suggests to expand the platform to iOS, adding and improving features that can be more optimal which one of it is Index of People Satisfaction feature, and enhancing socialization effort through cooperation with few parties so that the people of Bogor City can comprehend the importance of this application.